2023
DOI: 10.7717/peerj.15003
|View full text |Cite
|
Sign up to set email alerts
|

Paranoid thinking and perceived competitive intention

Abstract: Paranoid thinking, that others are hostile, can be seen even in the general population. Paranoia is considered the expectation that others are competitors who aim to maximize the differences in payoffs rather than maximize their own payoffs. This study examined whether paranoia reflects the irrational belief that others have a competitive intention and is associated with avoiding perceived competition. We recruited 884 US residents via the Internet and conducted a modified Dictator Game, in which monetary allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Perceptions of social threats induce individuals to cope with the perceived harm, and submission to perceived threats can also be viewed as a strategy that paranoid individuals may use in response to perceived harm (Freeman et al, 2005;Gilbert et al, 2005). Previous experimental studies have also reported that paranoia does not necessarily predict avoidance behavior toward social threats (Horita, 2023). This study suggests that the pathway stimulating social learning is not limited to the influence of the prestigious model and that learning through submission to superiors plays a role in human society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceptions of social threats induce individuals to cope with the perceived harm, and submission to perceived threats can also be viewed as a strategy that paranoid individuals may use in response to perceived harm (Freeman et al, 2005;Gilbert et al, 2005). Previous experimental studies have also reported that paranoia does not necessarily predict avoidance behavior toward social threats (Horita, 2023). This study suggests that the pathway stimulating social learning is not limited to the influence of the prestigious model and that learning through submission to superiors plays a role in human society.…”
Section: Discussionmentioning
confidence: 99%
“…However, paranoia is considered a continuum, and mild paranoia can be observed in the general population (Bebbington et al, 2013;Freeman et al, 2005Freeman et al, , 2011. Some empirical studies have investigated the cognitive and behavioral mechanisms of paranoia using non-clinical samples and have shown an association between paranoid thoughts and the tendency to attribute harmful intentions to others (Barnby et al, 2020;Comb et al, 2007;Greenburgh et al, 2019;Horita, 2021Horita, , 2023Raihani & Bell, 2017;Saalfeld et al, 2018).…”
Section: Introductionmentioning
confidence: 99%